Nitrogen and potassium concentrations in the nutrients solution for melon plants growing in coconut fiber without drainage - Gratieri, Luiz Augusto; Cecílio Filho, Arthur Bernardes [UNESP]; Barbosa, José Carlos [UNESP]; Pavani, Luiz Carlos [UNESP] (Wiley, 2013)
With the objective of evaluating the effects of N and K concentrations for melon plants, an experiment was carried out from July 1, 2011 to January 3, 2012 in Muzambinho city, Minas Gerais State, Brazil. The Bonus no. 2 was cultivated at the spacing of 1.1 × 0.4. The experimental design was a randomized complete block with three replications in a 4 × 4 factorial scheme with four N concentrations (8, 12, 16, and 20 mmol L-1) and four K concentrations (4, 6, 8, and 10 mmol L-1). The experimental plot constituted of eight plants. It was observed that the leaf levels of N and K, of N-NO3 and of K, and the electrical conductivity (CE) of the substrate increased with the increment of N and K in the nutrients' solution. Substratum pH, in general, was reduced with increments in N concentration and increased with increasing K concentrations in the nutrients' solution. Leaf area increased with increments in N concentration in the nutrients solution. Fertigation with solutions stronger in N (20 mmol L-1) and K (10 mmol L-1) resulted in higher masses for the first (968 g) and the second (951 g) fruits and crop yield (4,425 gm-2). © 2013 Luiz Augusto Gratieri et al.
Keywords: nitrogen; potassium; Brazil; climate; coconut; electric conductivity; fertigation; fruit set; harvest; leaf area; melon; moisture; nutrient; nutrient content; nutritional status; pH; plant growth; plant leaf; water retention; chemistry; dose response; drug effect; growth, development and aging; metabolism; Cocos; Cucumis melo; Dose-Response Relationship, Drug; Nitrogen; Potassium